The effect of dietary intervention and physical activities on the lipid profile of obese children - Fatimah Dewi Atikah; Nurzahara Siddik; Tiangsa Br Sembiring; Ani Ariani (Indonesian Pediatric Society Publishing House, 2009)
Background Obesity is defined as body weight increase due to excessive fat accumulation. Obesity during childhood and teenage years is related to cardiovascular risks including hyperinsulinism, hypercholesterolemia, decreased high density lipoprotein (HOI), and hypertension. The principles of managing obesity are reducing energy intake and increasing energy use, e.g., by increasing physical activities, changing life habits and, most importantly by involving family in the therapeutic process. Objective To evaluate the effect of dietary intervention and physical activity on obese children. Methods Seventy-six obese primary school children were randomly allocated to either receive intervention (diet and physical activities) or no intervention. At the beginning of the study, lipid profile was measured in all subjects. Subjects in the intervention group were asked to reduce calorie intake by 200 - 500 kCal per day, and participating in a walk of 20-30 minutes for five days per week over a period of one month. After one month, the lipid profile of both groups was remeasured and compared. Results After one month, 7 3 children had successfully completed the study and had complete data for analysis. There was a significant change in the mean HOL level before intervention (47.3 [SO 36.2] mg/dl) compared with after intervention (100.5 [SO 35.7] mg/dl, P<0.05) in the group where intervention was implemented. Conclusion There are no significant differences in serum lipid values after intervention in both groups.